2013
DOI: 10.1097/cin.0000000000000014
|View full text |Cite
|
Sign up to set email alerts
|

The Patient Perception of the Nurse-Patient Relationship When Nurses Utilize an Electronic Health Record Within a Hospital Setting

Abstract: Research has focused on electronic health record use during patient interactions primarily from a physician or advanced practice nurse perspective. Few if any empirical data exclusively explored the patient's hospital experience of the nurse-patient relationship when nurses use an electronic health record to communicate with them during patient interactions. The study was conducted to determine how use of a computer for documentation and care delivery influences communication dynamics between a nurse and patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Strauss [52] interviewed 11 patients about the dynamics with their nurses and the EMR. Similar to the qualitative evidence synthesis, participants described a positive perception of the EMR when the nurses acknowledged the participants before using the electronic device; however, many "expressed concerns [for] the privacy of their health record information."…”
Section: Qualitative Results: Clinician and Patient Experience In Dig...mentioning
confidence: 99%
See 2 more Smart Citations
“…Strauss [52] interviewed 11 patients about the dynamics with their nurses and the EMR. Similar to the qualitative evidence synthesis, participants described a positive perception of the EMR when the nurses acknowledged the participants before using the electronic device; however, many "expressed concerns [for] the privacy of their health record information."…”
Section: Qualitative Results: Clinician and Patient Experience In Dig...mentioning
confidence: 99%
“…A total of 18 studies (n=14, 78% qualitative and n=4, 22% mixed methods) with qualitative components were included in the qualitative evidence synthesis. Only 7% (1/15) of the qualitative studies in our review explored the patient experience in a digital hospital [ 52 ]; however, this study was excluded from the qualitative evidence synthesis and is reported narratively in the following paragraph. A total of 29% (2/7) of the mixed methods studies were also excluded for lacking direct participant quotes as per the exclusion criteria [ 50 , 75 ]; however, the quantitative results are reported in the previous sections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the nurse's back is to the patient while using the keyboard. According to Strauss,20 the computer screen should be located in the room so that the nurse and the patient can view the screen jointly. Patients (N = 11) reported that when they worked with the nurse while reviewing the data on the computer screen, they (the patients) experienced a positive connection with the nurse.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these studies focus on the way digital devices might be affecting the quality of service provided by health staff 5,7 , whereas others focus on the overhead caused by the multi-tasking between computer systems and the patient 8 . Often, these new artifacts have posed serious challenges to work practices, as they continually demand the attention of the health staff.…”
Section: Introductionmentioning
confidence: 99%